Valuing Crop Biodiversity: On-Farm Genetic Resources and Economic Change 2005
DOI: 10.1079/9780851990835.0192
|View full text |Cite
|
Sign up to set email alerts
|

Social institutions and seed systems: the diversity of fruits and nuts in Uzbekistan.

Abstract: This chapter builds on the household model presented in Chapter 5 [Missing markets, migration and crop biodiversity in the milpa system of Mexico: a household-farm model, by van Dusen, M. E., pp. 63-77] by exploring the role of social institutions in household access to planting material and use of crop biodiversity. Two types of institutions are analysed: (i) local community groups to which a household may belong and (ii) sources of planting material and agricultural information. Findings from a household sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…Currey [ 53 ] investigated diversity in home gardens in Kyrgyzstan and found a similar species composition, with an average of 6.4 species per home garden. Van Dusen [ 56 ] indicated an average of 4.9 fruit and nut tree species per home garden in Uzbekistan, similar to our average of 4.8 species per home garden in Uzbekistan in our study. Van Dusen [ 56 ] also found that the number of fruit trees varied largely (2–25 trees per garden in central parts of the valley he investigated, and 4–100 in more peripheral parts) depending on access to water.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Currey [ 53 ] investigated diversity in home gardens in Kyrgyzstan and found a similar species composition, with an average of 6.4 species per home garden. Van Dusen [ 56 ] indicated an average of 4.9 fruit and nut tree species per home garden in Uzbekistan, similar to our average of 4.8 species per home garden in Uzbekistan in our study. Van Dusen [ 56 ] also found that the number of fruit trees varied largely (2–25 trees per garden in central parts of the valley he investigated, and 4–100 in more peripheral parts) depending on access to water.…”
Section: Discussionsupporting
confidence: 90%
“…Van Dusen [ 56 ] indicated an average of 4.9 fruit and nut tree species per home garden in Uzbekistan, similar to our average of 4.8 species per home garden in Uzbekistan in our study. Van Dusen [ 56 ] also found that the number of fruit trees varied largely (2–25 trees per garden in central parts of the valley he investigated, and 4–100 in more peripheral parts) depending on access to water. Apple, persimmon, and walnut were preferred by households because they produce later in the year than most other trees and can be preserved during the cold period, when little to no fresh produce is available.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our investigation shows the importance of interaction in the development of horticulture in Central Asia. Van Dusen et al, 2006) Valuing Crop Biodiversity 3 3.6. Keywords Analysis, co-occurrence network.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of informal institutions are the social networks and village or town associations in which farmers often exchange seed or seed-related information. Many of these act indirectly on crop variety choices, since they exist for reasons other than the circulation of crop genetic material or products (Van Dusen et al 2006;Bela et al 2006).…”
Section: Introductionmentioning
confidence: 98%